Coadministration of antiepileptic drugs and P-glycoprotein inhibitors of flavonoid-type - Ferreira, Ana Filipa da Silva (2018)
The resistance to antiepileptic drugs (AEDs) remains a major unsolved therapeutic problem, which affects 30-40% of patients with epilepsy. The overexpression of multidrug efflux transporters, as the P-glycoprotein (P-gp), at the level of the blood-brain barrier of epileptic patients has been suggested as a key mechanism underlying the refractory epilepsy. Bearing this in mind, efforts have been made to search for therapeutically useful P-gp inhibitors. In an attempt to find potent and safer P-gp inhibitor drugs, a particular emphasis has been given to flavonoid compounds. Actually, apart from their potential value as P-gp inhibitors, these phytochemical compounds have been recognised as having a panoply of important pharmacological properties like anti-inflammatory, antioxidant, antitumoral, antimicrobial, antiviral, hormonal and even anticonvulsant effects. Taking this into account, the purpose of the present thesis was to conduct a comprehensive in vitro and in vivo evaluation of the potential of flavonoids as P-gp inhibitors, but also to explore a strategy of flavonoid/AED combined therapy as a possible approach to overcome the P-gp–mediated pharmacoresistance in epilepsy. This project involved the development and validation of appropriate and reliable bioanalytical techniques to support the accomplishment of the intended studies. Thus, high-performance liquid chromatography methods coupled with diode array detection (HPLC-DAD) were properly validated for the quantification of the target AEDs and some of their main metabolites in cell culture samples and in rat plasma and brain matrices. An additional HPLC-DAD technique was also developed to quantify several AEDs and metabolites in human plasma, which has shown to be a useful tool for the therapeutic drug monitoring in the clinical practice. According to the results of a set of in vitro assays, five out of eleven flavonoids tested, namely baicalein, (-)-epigallocatechin gallate [(-)-EPG], kaempferol, quercetin and silymarin demonstrated to have an interesting potential in inhibiting the P-gp activity. These promising flavonoids also promoted a significant increase in the intracellular accumulation of the AEDs carbamazepine (CBZ), oxcarbazepine (OXC) and phenytoin (PHT) and their active metabolites carbamazepine-10,11-epoxide (CBZ-E) and licarbazepine (LIC) in the Madin-Darby canine kidney cell line transfected with the human multidrug resistance-1 gene which encodes the human P-gp (MDCK-MRD1), showing up as important drug candidates to overcome the AED-resistance. Actually, excluding LTG, all the AEDs tested (CBZ, OXC and PHT) as well as their active metabolites (CBZ-E and LIC) were found to be P-gp substrates in the MDCK-MDR1 cells. Additionally, CBZ, CBZ-E, LIC, LTG, OXC and PHT promoted a statistically significant decrease of the intracellular concentration of rhodamine 123 (a classic P-gp probe substrate), suggesting an inducer effect on the functional activity of P-gp. An assessment of the potential synergic effects of baicalein, (-)-EPG, kaempferol, quercetin and silymarin on the P-gp inhibition was also performed, firstly in in vitro conditions and then in in vivo experiments. Indeed, when compared to their individual activity, some dual flavonoid combinations exhibited an increased potential in inhibiting the P-gp in the in vitro assays. Moreover, the dual combinations of (-)-EPG/silymarin and kaempferol/baicalein demonstrated a great potential in enhancing the intracellular accumulation of CBZ, OXC and PHT and their metabolites CBZ-E and LIC in the MDCK-MDR1 cells and such effects were comparable to those promoted by verapamil (the standard P-gp inhibitor). The effect of the combination of (-)-EPG/silymarin was also tested in transport assays of LIC (P-gp substrate) through MDCK-MDR1 cells mounted in Ussing chambers; as expected, this combination of flavonoids increased the apparent permeability coefficient of LIC. Overall, these in vitro findings were further supported by in vivo results. In fact, after the pretreatment of male Wistar rats with silymarin an increasing in the plasma concentrations of the studied AEDs (CBZ, OXC and PHT) was observed. Nevertheless, it should be highlighted that the main effects induced by silymarin were found on the OXC pharmacokinetics, for which was found a statistically significant increase in the peak plasma concentration (50%) and in the extent of systemic exposure (41%), having a direct impact on the drug concentrations reached in the brain. On the other hand, the use of dual combinations of (-)-EPG/silymarin on the inhibition of the activity of P-gp was also evaluated in vivo in Wistar rats, being noticeable the synergic potential of (-)-EPG/silymarin combinations in enhancing the degree of systemic exposure to OXC and LIC (a pharmacologically active metabolite of OXC), and it occurred in a comparable extent to that observed for verapamil (positive control). Indeed, the pretreatment of male Wistar rats with dual silymarin/(-)-EPG combinations originated peak plasma concentrations of OXC similar to those achieved in the presence of verapamil. Moreover, the effects promoted by silymarin/(-)-EPG combinations on the magnitude of systemic drug exposure were also reflected in the corresponding drug levels attained in the brain (biophase). Hence, according to our findings, it seems that the flavonoid/AED combined therapy can be thought as a promising approach that should continue to be exploited in order to overcome the P-gp–mediated pharmacoresistance. The availability of this in vitro and in vivo information also adds support to the efflux transporter hypothesis in explaining the pharmacoresistant epilepsy. Considering all its intrinsic potential and indisputable properties, the flavonoid-type compounds may emerge as an alternative to the available P-gp inhibitors for a prospective management of patients with drug-refractory epilepsy.